2019
DOI: 10.1167/iovs.18-26477
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of MicroRNA-34a, LGR4, EMT-Associated Factors, and MMP2 in Regulating Uveal Melanoma Cells

Abstract: PURPOSE. MicroRNA-34a (miR-34a) has been implicated in many biological processes. It is downregulated in uveal melanoma, and introduction of miR-34a inhibits the proliferation and migration of uveal melanoma cells. Leucine-rich repeat-containing G protein-coupled receptor 4 (LGR4) is a novel target of miR-34a identified first in retinal pigment epithelial cells. In this study, we sought to evaluate the interaction of miR-34a and LGR4 in uveal melanoma and its downstream mechanisms. METHODS. The expression of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
(58 reference statements)
0
15
0
1
Order By: Relevance
“…Transfection of miR-34a/b/c resulted in target protein downregulation and reduction in cell proliferation, invasion and migration [50,96]. Follow-on studies of miR-34a have reported its involvement in the regulation of LGR4, a universal tumour promoter, and downstream epithelial-to-mesenchymal transition proteins such as E-cadherin, N-cadherin, vimentin, SNAIL and MMP2 [97], such that downregulation of miR-34a lends to activation of epithelial signalling [97].…”
Section: Mirna As Tumour Suppressors In Ummentioning
confidence: 99%
“…Transfection of miR-34a/b/c resulted in target protein downregulation and reduction in cell proliferation, invasion and migration [50,96]. Follow-on studies of miR-34a have reported its involvement in the regulation of LGR4, a universal tumour promoter, and downstream epithelial-to-mesenchymal transition proteins such as E-cadherin, N-cadherin, vimentin, SNAIL and MMP2 [97], such that downregulation of miR-34a lends to activation of epithelial signalling [97].…”
Section: Mirna As Tumour Suppressors In Ummentioning
confidence: 99%
“…The EMT signaling pathway is further complicated by interactions with matrix metalloproteinases. Among these complex interactions, MMP2 and other MMPs have been demonstrated to promote EMT, which is involved in cancer invasion (43,44). The present study revealed that increased miR-30a-5p expression following curcumol treatment inhibited CRC cell invasion, migration and MMP2 expression, and activated the Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 50%
“…For example, KAI1 can suppress the progression of cancers of the digestive system via influencing invasion-associated protein metabolism (41). It also serves as an important tumor suppressor gene in the context of integumental tumors, with KAI1 inactivating mutations being a common feature in human melanoma (42). The ability of KAI1 to suppress oncogenesis is linked to its ability to inhibit the expression of AP-1, JUNB, poly (ADP-ribose) polymerase (PARP) and other oncogenes (43).…”
Section: Discussionmentioning
confidence: 99%